EXPLORING THE IMPACT OF SUSTAINABLE HUMAN RESOURCES MANAGEMENT ON THE EFFICIENCY AND EFFECTIVENESS OF CONSTRUCTION PROJECTS: THE CASE OF IRAQ - Abbas Abdulameer Khalaf (Scholars Digest Publishing, 2024)
This study investigates the impact of sustainable human resource management (HRMM) on the performance of building projects in Iraq. Human Resource Management (HRM) is essential for the success of construction projects. This study examines sustainable HRM methods that might enhance the overall performance of organizations engaged in project management. Research indicates that implementing sustainable HRM practices can enhance employee engagement and productivity, elevate the standard of work, foster effective communication and collaboration within teams, so positively impacting the outcomes of construction projects. The study examines three construction firms operating in Iraq. A total of fifteen participants were interviewed in order to collect their perspectives on the Human Resource Management (HRM) practices that have been adopted in their business and the resulting effects on project performance. The qualitative methodology relies on conducting semi-structured interviews with individuals. The snowball sampling technique was employed to enlist participants, ensuring a thorough survey of HRM practices across various construction firms in Iraq. The findings suggest that the examined organizations apply diverse HRM strategies to attract, cultivate, and incentivize their personnel. Tangible instances of achievement encompass training and development programs, initiatives to maintain a healthy work-life balance, and mechanisms that acknowledge and reward exceptional performance. Nevertheless, the participants also acknowledged the presence of challenges, such as the administration of temporary agreements that can impact the stability and drive of employees. Enhancements are recommended, namely in regards to the exchange of information and openness inside organizations. To summarize, this study emphasizes the significance of implementing sustainable human resource management practices in the construction industry in Iraq. Implementing efficient human resource management (HRM) strategies can have a beneficial impact on project performance by fostering employee engagement and enhancing productivity. Nevertheless, it is crucial to tackle the highlighted obstacles and implement measures to continuously enhance HRM processes in order to fully capitalize on these advantages.
Keywords: Exploring, Sustainable Human, Resources Management, On the Efficiency, Effectiveness, Construction Projects, Iraq.